Medical students’ perception of paid E-learning - Parsa Mohri; Yilmaz Onat Koyluoglu; Mustafa Ege Seker; S‚ehla Nurefs‚an Sancak; Mirkan Dikeç; Ayça Aydemir Mazlumoglu; Yesim Gurol; Ilhan Cem Sungur (PLoS ONE, 2025)
Background In addition to the medical school curriculum, medical students often take the initiative to incorporate external paid digital educational resources, especially during the pandemic. In this study, we organized an exemplary questionnaire method to enable evidence-based decisions before providing paid e-learning resources to medical students. Methods An online form was distributed to all registered medical students at a Turkish medical school, and the compiled responses were subjected to statistical analysis. The participants were queried about their general background, post-graduation plans, use of study materials, purpose and perceived benefits of utilizing paid e-learning resources, as well as any financial burden or opinions regarding the associated costs. Results A total of 119 medical students participated in the online form. The findings revealed that 87% of the participants reported using paid e-learning resources for school exams, with 71.5% of them indicating an improvement in their exam scores. Approximately 26.1% of the participants did not specify any change. When asked to rate the cost of using paid e-learning resources on a scale of 1 to 10, the average score was 8.6 ± 1.58. Furthermore, 40% of the participants relied on repeated free demo sessions, while only 27% reported paying the fees associated with these resources. Conclusions With the evolution of medical education, particularly in the aftermath of the pandemic, medical students are increasingly seeking to supplement their medical curriculum, pursue self-interests, and engage in extracurricular research by utilizing paid e-learning resources. However, the costs associated with these resources often prevent some students from fully benefiting from them. Therefore, it is essential for medical schools to make evidence-based decisions to support their students, recognizing that digitally available resources play an integral role in the assimilation of medical education.